Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS): Post-Exertional Malaise and the Biology of Energy Failure - Szafraniec, Artur; Krężel, Olga; Krężel, Maciej; Kalinowska, Zuzanna; Aleksandrowicz, Hanna; Rybińska, Marcelina (Journal of Education, Health and Sport, 2026)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a severe, heterogeneous multisystem disorder defined by persistent fatigue lasting ≥6 months that is disproportionate to exertion, not relieved by rest, and associated with substantial functional decline. Its hallmark feature is post-exertional malaise (PEM), a delayed and prolonged worsening of symptoms after minimal physical or cognitive effort. Common symptoms include unrefreshing sleep, cognitive impairment, pain, flu-like complaints, sensory hypersensitivity, and autonomic dysfunction such as orthostatic intolerance. Diagnosis is clinical and requires exclusion of alternative medical and psychiatric conditions, with commonly used frameworks including the CDC/Fukuda and International Consensus Criteria. Evidence supports a multifactorial pathophysiology involving immune dysregulation, metabolic and mitochondrial abnormalities, neuroendocrine disturbance, gut dysbiosis, and autonomic dysfunction - collectively suggesting impaired energy homeostasis. No validated biomarker exists, though multi-omic immune and metabolic signatures remain under investigation. Management is supportive, emphasizing individualized pacing and treatment of comorbidities.